A conservative compact difference scheme for the coupled Klein–Gordon–Schrödinger equation. Issue 5 (23rd March 2013) - Sun, Qihang; Zhang, Luming; Wang, Shanshan; Hu, Xiuling
Abstract In this article, a conservative compact difference scheme is presented for the periodic initial‐value problem of Klein–Gordon–Schrödinger equation. On the basis of some inequalities about norms and the priori estimates, convergence of the difference solution is proved with order O(h4 +τ 2) in maximum norm. Numerical experiments demonstrate the accuracy and efficiency of the compact scheme. © 2013 Wiley Periodicals, Inc. Numer Methods Partial Differential Eq, 2013